Almost all derivative quivers of artinian biserial rings contain chains - Avdeeva, T.; Ganyushkin, O. (Algebra and Discrete Mathematics, 2003)
A lower estimate for the number Mn of all labelled quivers with n–vertex parts of Artinian biserial rings is given and the asymptotic of the relation Mn/Bn, where Bn denotes the number of those quivers all connected components of which are cycles, is studied.